Effect of N fertility rate on internal drainage under irrigated corn in central North Dakota - Wienhold, Brian J., author; Trooien, Todd P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
Wetlands present in irrigated areas may be subject to groundwater discharge. The potential exists for contamination if these water inputs contain agricultural chemicals. Irrigation scheduling and fertilizer management are two aspects of irrigated crop management that influence the potential for nitrate (NO3) contamination of groundwater. Meteorological methods of scheduling irrigation are becoming more accessible to producers. These methods utilize weather data to estimate potential evapotranspiration (ET) and incorporate a crop coefficient to adjust for the water requirements of different crops and growth stages. Nitrogen fertilizer is the agricultural chemical used in the greatest quantities and is also the most commonly detected contaminant in ground waters. Efficient fertilizer management involves applying sufficient fertilizer to meet a yield goal with adjustments in the fertilizer rate for residual fertilizer N in the soil and additions in crop residue, manure, and irrigation water. We have been measuring com yield, internal drainage, and determining the fate of applied N in lysimeters at two sites in central North Dakota. Lysimeters were fertilized to 90 or 180 lbs N a-1 (100 or 200 kg N ha-1) with the higher rate being the rate recommended for an optimum crop yield. Irrigation was applied such that precipitation plus irrigation equaled the calculated ET rate. Averaged over years, com receiving 180 lbs N a-1 yielded 30% more dry matter; had a 40% greater N content; and derived 40% more N from fertilizer than com receiving 90 lbs N a-1. The meteorological method estimated water use by the com crop receiving 180 lbs N a-1 well as only 6% of the applied water drained out of the root zone. In contrast, over 20% of the applied water drained out of the root zone of lysimeters receiving 90 lbs N a-1. Reduced growth of the under fertilized crop resulted in poor utilization of applied irrigation. Inadequate fertilization not only reduced yield but resulted in an increase in leaching potential of agricultural chemicals.
1996 USCID wetlands seminar
Not digitized by CSUL Digital Services.
Presented at Water for agriculture and wildlife and the environment: win-win opportunities: proceedings from the USCID wetlands seminar on June 27-29, 1996 in Bismarck, North Dakota.